Utilizing Local Resources Of Ijuk Aren To Produce Clear Water In Gegerung Village, Lingsar District, Lombok Barat District, NTB - Nurchayati Nurchayati; A. G. Ulayya; J. A. Ramadhan; L. W Agusti W; B.T. E. Kurnia (JURNAL KARYA PENGABDIAN, 2023)
Clean water is one of the main human needs in everyday life is very important to pay attention to its quality. Unfortunately there are still many areas that cannot enjoy clean water as it should. One of the villages that has low water quality is Gegerung Village, Lingsar District, West Lombok Regency. With a variety of natural resources owned by Gegerung Village, the Mataram University Community Service Team took the initiative to make a water filter made from natural palm fiber to overcome existing water problems. Natural materials used include river stone, gravel, palm fiber, and fine river sand. The material is stacked until it fills the tub, then the water is flowed to get clear water. Keywords : Water quality, local resources, palm fiber